PERKAWINAN DIBAWAH UMUR DAN IMPLIKASINYA TERHADAP KEHARMONISAN RUMAH TANGGA - Dirga Juhayati dan Joni Zulhendra (Fakultas Hukum Universitas Tamansiswa Padang, 2021)
Factors causing underage marriages and their implications for household harmony. Family harmony is the achievement of happiness, peace, full of affection, and good communication for each family member and there is very little conflict or if a conflict occurs, the family is able to resolve it well. With the complex implications of early marriage on family life, the harms outweigh the benefits. Many factors cause early marriage, namely as follows: firstly because of promiscuity, the result of promiscuity has negative and deviant behavior, because when pacara often does bad things. Second, because of economic factors, due to economic weakness which causes marriage at an early age so that it does not become a burden on the parents, the third is due to educational factors where teenagers who marry at an early age do not want to continue their education anymore, because of promiscuity or economic factors are reasons for not wanting to continue his education